Effectiveness of Mangrove Forest as Coastal Protection along the West Coast of Northern Peninsular Malaysia - Hashim, A.M. (EDP Sciences, 2016)
The effectiveness of mangrove forest as coastal protection was evidenced during Indian Ocean Tsunami (IOT) on 24th December 2004. This paper presents the assessment on the characteristics and distribution of the mangrove forest along three northern states (Perlis, Kedah and Perak) affected by IOT 2004. At each site, the characteristics of individual tree were recorded including their species, height and diameter at breast height (DBH). A total of 52 matured trees were sampled that encompassing four species; A. marina (n=21), A. alba (n=7), R. mucronata (n=20) and R. apiculata (n=4) were found with A. marina as the dominant species. The zonation of mangrove forest along the northern states revealed that Avicenniacea inhabits the frontal area. The field survey also discovered that mangrove forest along the states was generally insufficient to protect the coastal area from future tsunami. There were several rehabilitation programs that had been implemented, but not all replanting efforts were successful. Outcomes from this research provided invaluable findings for the optimum replanting scheme to ensure acceptable level of protection along Malaysia's coastline. Â© The Authors, published by EDP Sciences, 2017.